A modified effective path length for predicting rain attenuation based on measurements in Penang-Malaysia - Lwas, Ali Kadhim; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Mandeep, Singh Jit; Ismail, Ahmad Fadzil; Daoud, Jamal Ibrahim; Zyoud, Alhareth (Asian Research Publishing Network (ARPN), 2015)
A modification to an effective path length for predicting rain attenuation in Malaysia is proposed in this paper. Due to the scarcity of actual signal measurements at higlh frequencies-bands in tropical climates make predicted models are key resource for generating rain attenuation. A modification to calculate the effective path length is introduced in the original model. A control parameter rb.o is also induced based on the rain intensity variations along the slant path. A new value is suggested according to measurements in Malaysia. The results showed that modified rain attenuation model has significantly improved the rain attenuation prediction in Malaysia